2021
DOI: 10.31803/tg-20201008090615
|View full text |Cite
|
Sign up to set email alerts
|

Gamification Framework for E-Learning Systems in Higher Education

Abstract: This paper explains the concept of gamification, lists the current models according to which educational e-courses can be designed, and proposes a conceptual eRIOOS model aimed at higher education. The aim of the research as well as the purpose of creating a conceptual model of gamification is to standardize the elements of computer games that can be used in educational e-courses at higher education institutions. In the preparation of this research, the emphasis was placed on the invention and analysis of prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…If the E-learning system is designed correctly, the student creates a sense of comfort that can lead to a state of flow in which the learning process is optimal. This is one of the conclusion by Bernik [4] within the manuscript where gamification framework was described.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…If the E-learning system is designed correctly, the student creates a sense of comfort that can lead to a state of flow in which the learning process is optimal. This is one of the conclusion by Bernik [4] within the manuscript where gamification framework was described.…”
Section: Introductionmentioning
confidence: 56%
“…The problem observed in the research of de-Marcos et al, in which the experimental groups of respondents showed very little interest in teaching materials and where approximately 20% of students actively participated in the study, will be particularly monitored in this study in order to avoid repeating the same. Also, the seven elements of computer games (points, levels, success scale, badges, explanation for a beginner, social loops, and gradual unlocking of content) that Iosup and Epema list, were considered for inclusion in the gamified system, along with other elements described in Bernik [4], with the aim of confirming the results cited by Iosup and Epema [11].…”
Section: Research Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Chou ( 2015 ) A gamification framework called Octalysis which is based on eight motivational drivers arranged in an octagonal shape. The elements of the Octalysis model that are in the right part represent are related to intrinsic motivation, as opposed to the elements on the left side, which relate to extrinsic motivation (Bernik, 2021 ). The elements at the top of the system are considered to be positive motivators that encourage the improvement of knowledge and skills through meaning and various incentives, whereas the elements at the bottom of the system are considered negative motivators that encourage bad emotion and should be minimized when planning and implementing the system (Bernik, 2021 ) 6.…”
Section: Results Of the Searchmentioning
confidence: 99%
“…Gamification was first applied as a digital marketing strategy to enhance customer participation [33]. Because it can effectively stimulate specific behaviours and result in happiness, gamification has begun to be applied in other fields, such as education [11,12,22,24,27,57], health care [18,30,36,62,79], organizational effectiveness [46,66], software development [56], software design [55,68], e-commerce [5,9,53] and marketing [58,76].…”
Section: Introductionmentioning
confidence: 99%